2023
DOI: 10.3390/gels9070515
|View full text |Cite
|
Sign up to set email alerts
|

Statistically Optimized Tacrolimus and Thymoquinone Co-Loaded Nanostructured Lipid Carriers Gel for Improved Topical Treatment of Psoriasis

Abstract: The aim of this investigation was to develop and analyze a tacrolimus and thymoquinone co-loaded nanostructured lipid carriers (TAC-THQ-NLCs)-based nanogel as a new combinatorial approach for the treatment of psoriasis. The NLCs were formulated by an emulsification-solvent-evaporation technique using glyceryl monostearate, Capryol 90 (oil), and a mixture of Tween 80 and Span 20 as a solid lipid, liquid lipid, and surfactant, respectively. Their combination was optimized using a three-factor and three-level Box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The infrared spectra of NLC, NLC–chitosan sol, and NLC–chitosan hydrogel beads were obtained by FTIR spectrometer (Nicolet 6700, Thermo Scientific, Madison, WI, USA) [ 57 ]. The scanning range was from 4000 to 800 cm −1 , with a total of 32 scans.…”
Section: Methodsmentioning
confidence: 99%
“…The infrared spectra of NLC, NLC–chitosan sol, and NLC–chitosan hydrogel beads were obtained by FTIR spectrometer (Nicolet 6700, Thermo Scientific, Madison, WI, USA) [ 57 ]. The scanning range was from 4000 to 800 cm −1 , with a total of 32 scans.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasonication with a probe type sonicator (Hielscher, UP-50H, Stahnsdorf, Germany) was then used for 3 minto further reduce the particle size (PS) after the lipid phase was transferred drop-wise with the help of syringe into the aqueous form which being stirred at a constant rotation at magnetic stirrer with 1000 rotation per minute (Remi-Elektrotechnik Ltd., Mumbai, India). The systematic optimization of the formulation composition was performed and has been discussed in the subsequent sections ( Alam et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Their research indicated that this nanogel formulation showed promise as a combined treatment for psoriasis. Moreover, it demonstrated the ability to reduce the toxicity typically associated with escalating dosages [ 105 ].…”
Section: Current Nanotechnology-based Approaches For the Topical Trea...mentioning
confidence: 99%